Sintese de derivados triazólicos do adamantano com potencial atividade fungicida frente a Fusarium solani f. sp. Piperis - Ferreira, Lara Chaves de Freitas (2024)
Black pepper is a spice widely used since antiquity and is considered a valuable product for the agribusiness industry. The state of Espírito Santo is the largest producer of black pepper in Brazil, thus holding significant importance in the national economic scenario. However, black pepper cultivars suffer from large-scale fungal infections, with Fusarium solani being one of the main contributors to the reduced lifespan of black pepper plants. In the quest for discovering new, more effective molecules against fungal diseases, understanding their modes of action is crucial. Commercially available agrochemicals can inhibit fungal growth by inhibiting the enzyme succinate dehydrogenase, which is vital for the electron transport chain. Compounds containing the 1,2,3-triazole or adamantane nucleus exhibit numerous biological activities, including antifungal properties. The 1,2,3- triazole ring is solely obtained through synthetic means, commonly synthesized via copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC), following the "click chemistry" strategy. Accordingly, eight new adamantane-derived triazoles, 32a-c and 33a-e, were synthesized for evaluation of their activity against F. solani. Additionally, potential interactions of the new triazoles with the succinate dehydrogenase enzyme were assessed through molecular docking studies. The compounds interacted with the ubiquinone binding site of SDH through various hydrogen bonds, hydrophobic interactions, and π-stacking interactions, with 33e being the best compound in terms of interaction with the enzyme. It formed hydrogen bonds with the same amino acid residues as DNT, the original ligand of PBD 1NEN. The structures of the triazoles have been elucidated so far by 1H, 13C NMR, HSQC, HMBC, COSY, and Infrared spectroscopy, and subsequent mass spectrometry analyses will be conducted